Serine/threonine protein kinase 25 antisense oligonucleotide treatment reverses glucose intolerance, insulin resistance, and nonalcoholic fatty liver disease in mice. Issue 1 (20th November 2017) - Nuñez‐Durán, Esther; Aghajan, Mariam; Amrutkar, Manoj; Sütt, Silva; Cansby, Emmelie; Booten, Sheri L.; Watt, Andrew; Ståhlman, Marcus; Stefan, Norbert; Häring, Hans‐Ulrich; Staiger, Harald; Borén, Jan; et al.
Abstract : Nonalcoholic fatty liver disease (NAFLD) contributes to the pathogenesis of type 2 diabetes and cardiovascular disease, and patients with nonalcoholic steatohepatitis (NASH) are also at risk of developing cirrhosis, liver failure, and hepatocellular carcinoma. To date, no specific therapy exists for NAFLD/NASH, which has been recognized as one of the major unmet medical needs of the twenty‐first century. We recently identified serine/threonine protein kinase (STK)25 as a critical regulator of energy homeostasis and NAFLD progression. Here, we investigated the effect of antisense oligonucleotides (ASOs) targeting Stk25 on the metabolic and molecular phenotype of mice after chronic exposure to dietary lipids. We found that Stk25 ASOs efficiently reversed high‐fat diet‐induced systemic hyperglycemia and hyperinsulinemia, improved whole‐body glucose tolerance and insulin sensitivity, and ameliorated liver steatosis, inflammatory infiltration, apoptosis, hepatic stellate cell activation, and nutritional fibrosis in obese mice. Moreover, Stk25 ASOs suppressed the abundance of liver acetyl‐coenzyme A carboxylase (ACC) protein, a key regulator of both lipid oxidation and synthesis, revealing the likely mechanism underlying repression of hepatic fat accumulation by ASO treatment. We also found that STK25 protein levels correlate significantly and positively with NASH development in human liver biopsies, and several common nonlinked single‐nucleotide polymorphisms in the human STK25 gene are associated with altered liver fat, supporting a critical role of STK25 in the pathogenesis of NAFLD in humans. Conclusion : Preclinical validation for the metabolic benefit of pharmacologically inhibiting STK25 in the context of obesity is provided. Therapeutic intervention aimed at reducing STK25 function may provide a new strategy for the treatment of patients with NAFLD, type 2 diabetes, and related complex metabolic diseases. ( Hepatology Communications 2018;2:69–83)